The Prevalence of Depression Among Parkinson’s Disease Patients in Saudi Arabia: A Cross-Sectional Study - Al-Qahtani Z; Alqahtani ASM; Alzuhairi AMS; Qarah M; Alqarni AA; Alqahtani AOM; AlShehri FAA; Alqathanin MAA; Alshahrani OMO; Alqahtani MAF; Mahmood SE (Neuropsychiatric Disease and Treatment)
Zainah Al-Qahtani,1 Abdulrahman Saad M Alqahtani,2 Abdulmohsin Mohammed S Alzuhairi,3 Mohammed Qarah,4 Albara A Alqarni,3 Abdulaziz Othman M Alqahtani,5 Fahad Abdullah A AlShehri,3 Muath Abdullah A Alqathanin,6 Omair Mohammed O Alshahrani,3 Mohammed Ali F Alqahtani,5 Syed Esam Mahmood7 1Neurology Section, Internal Medicine Department, College of Medicine, King Khalid University, Abha, 61421, Saudi Arabia; 2Aseer Cluster Health, Abha, Saudi Arabia; 3King Khalid University, Abha, Saudi Arabia; 4Public Health Department, Saudi Board of Preventive Medicine, Madinah, Saudi Arabia; 5College of Medicine King Khalid University, Abha, Saudi Arabia; 6Internal Medicine Department, Saudi Board of Internal Medicine, Abha, Saudi Arabia; 7Department of Family and Community Medicine, College of Medicine, King Khalid University, Abha, 61421, Saudi ArabiaCorrespondence: Syed Esam Mahmood, Department of Family and Community Medicine, College of Medicine, King Khalid University, Abha, 62529, Saudi Arabia, Email smahmood@kku.edu.saBackground and Aim: Depression is thought to affect up to half of Parkinson’s patients at some point during their illness, while anxiety is reported by about 40% of PD patients. The study aimed to assess the prevalence of depression and anxiety among patients with Parkinson’s disease (PD) in Saudi Arabia.Methods: The study involved Saudi Arabian citizens and residents aged 40 or older with PD, who completed internet-survey (including online and email-based data collection) or telephone-survey by trained interviewers. We used the Parkinson’s Disease Questionnaire for quality-of-Life assessment questionnaire (PDQ-39), Patient Health Questionnaire-9 for depression (PHQ-9), and General Anxiety Disorder-7 anxiety questionnaire (GAD-7).Results: The study included 46 participants, of whom 37% were aged 60– 69 years, 67% were male, 46% had completed a university education, and 87% were married. Depression symptoms were present in 84.8% of participants, while 73.9% experienced anxiety. PD patients lacking social support were 8 times more likely to develop major depression [OR = 8.27, 95% CI (1.47– 46.31), p = 0.016] and 5 times more likely to experience anxiety symptoms [OR = 5.36, 95% CI (1.14– 25.26), p = 0.034]. Those unable to perform daily living activities or who faced stigma had a 16.5 times higher likelihood of anxiety symptoms [OR = 16.5, 95% CI (1.62– 168.48), p = 0.018]. Furthermore, cognitive impairment increased the likelihood of anxiety by 11 times [OR = 11.43, 95% CI (1.83– 71.42), p = 0.009].Conclusion: The study reveals a high prevalence of depression and anxiety among Parkinson’s disease patients, linked to physical impairments and social isolation. Many patients report no mental health improvement despite treatment, highlighting the need for routine mental health assessments, social support, and tailored interventions to enhance their quality of life. The small sample size may limit the statistical power, precision, and generalizability of the study’s findings.Keywords: Parkinson disease, depression, anxiety, Saudi Arabia